2020
DOI: 10.3389/fonc.2020.01668
|View full text |Cite
|
Sign up to set email alerts
|

Priming of Anti-tumor Immune Mechanisms by Radiotherapy Is Augmented by Inhibition of Heat Shock Protein 90

Abstract: Ernst et al. HSP90i Augments Radiotherapy-Induced Immune Priming priming of allogeneic T cell responses in vitro. In summary, HSP90 inhibition-apart from its radiosensitizing potential-obviously enables and supports the initial steps of anti-tumor immune priming upon radiotherapy and thus represents a promising partner for combined modality approaches. The therapeutic performance of such strategies requires further in-depth analyses, especially for but not only limited to CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…The HSP90 inhibitor NW457 ( epi -pochoxime F) was previously described ( 27 31 ). For in vitro experiments, a 10 mM stock solution was prepared in DMSO (Sigma-Aldrich, Taufkirchen, Germany) and was further diluted to 100 µM with DMSO before final concentrations were adjusted in cell culture medium.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HSP90 inhibitor NW457 ( epi -pochoxime F) was previously described ( 27 31 ). For in vitro experiments, a 10 mM stock solution was prepared in DMSO (Sigma-Aldrich, Taufkirchen, Germany) and was further diluted to 100 µM with DMSO before final concentrations were adjusted in cell culture medium.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were seeded into Ibidi µ-slides supplemented with culture inserts (both from Ibidi) and allowed to adhere overnight. Cells were treated with 30 nM NW457 or DMSO for 24 h, irradiated at 3 Gy, and live-cell imaging was performed for 12 h. Images were captured in intervals of 3 min, and cell migration was analyzed using the manual tracking plugin tool (ImageJ) as previously described ( 31 , 34 ). Migration was quantified in form of colonized area (four regions of interest per condition in three independent experiments) and accumulated distance per cell over time (at least 25 randomly picked cells per condition).…”
Section: Methodsmentioning
confidence: 99%
“…Astonishingly, the specific immune response may also be subject to secondary interferences. In this regard it could be shown that HSP90 inhibitors strongly increase immune priming of tumor cells after irradiation [84].…”
Section: Radiation Biology On the Move Advances In Radiation Biology-mentioning
confidence: 99%
“…As HSP90 stabilises numerous crucial proteins in tumor growth, it has the capacity to be a promising biomarker for diagnosis and prognosis and may be of therapeutic value for monitoring various cancers (Kryeziu et al, 2019). HSP90 is also a potential target for anti-cancer treatment, e.g., HSP90 inhibitors have become popular candidates for anti-cancer therapy (Ernst et al, 2020). Studies have indicated that HSP90 may be positively involved in the development of HCC and may provide a potential biomarker for monitoring advanced HCC (Qin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%